Highly active and durable carbon electrocatalyst for nitrate reduction reaction. (15th September 2019) - Duan, Weijian; Li, Ge; Lei, Zhenchao; Zhu, Tonghe; Xue, Yuzhou; Wei, Chaohai; Feng, Chunhua
Abstract: The development of a new class of carbon electrocatalysts for nitrate reduction reaction (NRR) that have high activity and durability is extremely important, as currently reported metallic electrocatalysts show a main drawback of low stability owing to leaching and oxidation. Herein, we demonstrate that a unique N-doped graphitic carbon-encapsulated iron nanoparticles can be utilized as a promising NRR electrocatalyst. The resulting Fe(20%)@N–C achieves a better nitrate removal proportion of 83.0% (attained in the first running cycle) compared to the efficiencies of other reference catalysts, including those with lower entrapped Fe content. The nitrogen selectivity is 25.0% in the absence of Cl − and increases to 100% when supplemented with 1.0 g L −1 NaCl. More importantly, there is no statistically significant difference (at a 95% confidence interval) regarding the removal percentage recorded over 20 cycles for the Fe(20%)@N–C cathode. We propose that the iron nanoparticles could attenuate the work function on the neighboring carbon atoms, which are the reactive sites for NRR, and that the graphitic shells hinder the access of the electrolyte, thus protecting the iron particles from dissolution and oxidation. Testing with the real industrial wastewater further demonstrates the superiority of Fe(20%)@N–C cathode towards NRR, as evidenced by efficient removal of nitrate available in the biological effluent from a local coking wastewater treatment plant. Graphical abstract: Image 1 Highlights: A new class of carbon electrocatalysts are developed for nitrate reduction reaction. A unique N-doped graphitic carbon-encapsulated iron nanoparticles is synthesized. The carbon electrocatalyst exhibits high activity and durability. The performance can be attenuated by the amount of iron in the catalyst. Efficient removal of nitrate in the coking wastewater is achieved.